GENERAL RELATIVITY AND ITS APPLICATIONS black holes, compact stars and gravitational waves. - Ferrari, Valeria, 1952-; Gualtieri, Leonardo, 1971-; Pani, Paolo (Astrophysicist) ([S.l.] : CRC PRESS, 2020)
Containing the latest, groundbreaking discoveries in the field, this text outlines the basics of Einstein's theory of gravity with a focus on its most important astrophysical consequences, including stellar structures, black holes and the physics of gravitational waves. Blending advanced topics - usually not found in introductory textbooks - with examples, pedagogical boxes, mathematical tools and practical applications of the theory, this textbook maximises learning opportunities and is ideal for master and graduate students in Physics and Astronomy. Key features:Provides a self-contained and consistent treatment of the subject that does not require advanced previous knowledge of the field.Explores the subject with a new focus on gravitational waves and astrophysical relativity, unlike current introductory textbooks.Fully up-to-date, containing the latest developments and discoveries in the field.
OCLC-licensed vendor bibliographic record.
Keywords: General relativity (Physics); Gravitation; Gravitational waves; SCIENCE / Astrophysics & Space Science; SCIENCE / Mathematical Physics; SCIENCE / Physics